Corrigendum: Traditional uses, phytochemistry, pharmacology and toxicology of garlic (Allium sativum), a storehouse of diverse phytochemicals: a review of research from the last decade focusing on health and nutritional implications - Tudu, Champa Keeya; Dutta, Tusheema; Ghorai, Mimosa; Biswas, Protha; Samanta, Dipu; Oleksak, Patrik; Jha, Niraj Kumar; Kumar, Manoj; Radha; Proćków, Jarosław; Pérez de laLastra, José M; Dey, Abhijit (Frontiers in nutrition, 2024)
[This corrects the article DOI: 10.3389/fnut.2022.929554.].